On the Bayesian approach to forensic age estimation of living individuals. (December 2017) - Sironi, Emanuele; Vuille, Joëlle; Morling, Niels; Taroni, Franco
Highlights: Forensic evidence interpretation is a fundamental aspect of forensic work. Evidence interpretation in forensic age estimation still need of conceptual developments. Inductive reasoning, which is fundamental in the forensic evidence interpretation, has a Bayesian core. Abstract: Forensic age estimation, a branch of forensic science, has received renewed attention lately mainly due to societal migration phenomena. And yet, the interpretation of age-related evidence is still largely neglected as a field, the literature being usually limited to technical discussions strictly pertaining to the statistical methodologies to be used in estimation process. This short communication aims to highlight the fundamental role of evidence evaluation and interpretation in forensic age estimation. We illustrate why the Bayesian approach represents the best choice in such a perspective.